Automatic SemanticRole Annotation for Portuguese - Bick, Eckhard (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2007: Anais do V Workshop em Tecnologia da Informação e da Linguagem Humana, 2007)
This paper describes an automatic annotation system for semantic roles, implemented as an independent addon module for syntactically parsed text. The formalism uses handwritten Constraint Grammar (CG) rules to map and disambiguate 40 different semantic roles. As a proofofconcept, an evaluation on treebank data was performed, where the system achieved an average Fscore of 88.6.